Safety and feasibility of transulnar catheterization when ipsilateral radial access is not available - Kedev, Sashko; Biljana Zafirovska; Dharma, Surya; Petkoska, Danica (Wiley, 2014)
We evaluated the safety and feasibility of transulnar approach when ipsilateral radial access was not available.